Handling multiplicity due to multiple primary or composite endpoints in clinical trials - Sankoh, Abdul (Henry Stewart Talks, 2007)
The complexities of a clinical trial with multiple objectives and/or therapeutic areas where the disease manifests itself in a multi-faceted manner, Reasons for and the common sources of multiplicity in clinical trials, The associated clinical and statistical approaches for controlling the probability of incorrectly declaring a treatment benefit
Archived at 2018/05/31